2016
DOI: 10.1039/c6cc02362b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of meta-substituted [18F]3-fluoro-4-aminopyridine via direct radiofluorination of pyridine N-oxides

Abstract: Due to their electron-rich aromatic structure, nucleophilic (radio)fluorination of pyridines is challenging, especially at the meta position. In this paper, we describe the first example of direct fluorination of a pyridine N-oxide to produce a metafluorinated pyridine. Specifically, fluorination of 3-bromo-4-nitropyridine N-oxide produced in several minutes 3-fluoro-4-nitropyridine N-oxide in moderate yield at room temperature. This intermediate compound was later converted to 3-fluoro-4-aminopyridine easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This is due to the increased level of expression of K v 1 channels in those areas as well as the increased accessibility of the drug to the channels given the lack of myelin 19,20,29,30 . It has also been reported that 3F4AP can be labeled with fluorine-18 [31][32][33] and that radiofluorinated [ 18 F]3F4AP can be used to detect chemically-induced demyelinated lesions in rat brains using PET 27 . The high sensitivity of this tracer towards demyelination makes it a promising candidate for imaging many neurological diseases where there is demyelination including MS, TBI, SCI, stroke, AD, and others 30 .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the increased level of expression of K v 1 channels in those areas as well as the increased accessibility of the drug to the channels given the lack of myelin 19,20,29,30 . It has also been reported that 3F4AP can be labeled with fluorine-18 [31][32][33] and that radiofluorinated [ 18 F]3F4AP can be used to detect chemically-induced demyelinated lesions in rat brains using PET 27 . The high sensitivity of this tracer towards demyelination makes it a promising candidate for imaging many neurological diseases where there is demyelination including MS, TBI, SCI, stroke, AD, and others 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The overall radiochemical yield was comparable with the manual synthesis with a specific activity of 37 to 148 GBq/μmol (n = 12). As reported in the recent literature, this tracer was synthesized with 2.5% (noncorrected) of radiochemical yield and with a specific activity of 0.37 to 3.7 GBq/μmol.…”
Section: Resultsmentioning
confidence: 99%
“…They prepared the fluorine‐18 analog of 3‐fluoro‐4‐aminopyridine (Scheme ) by halogen (Br or F) exchange followed by hydrogenation. Nevertheless, this method suffered from low overall radiochemical yield or low specific activity . Therefore, new methods to prepare fluorine‐18 labeled 3‐fluoro‐4‐aminopyridine in better radiochemical yield and higher specific activity are warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, 4AP blocks the exposed K + channels and therefore enhances conduction 16,17,19,20,[29][30][31][32] . Recently, it has been shown that the fluorinated derivative 3-fluoro-4-aminopyridine (3F4AP) also binds to these channels 33 and, once labeled with 18 F, can serve to detect areas of demyelination using positron emission tomography (PET) [33][34][35][36][37] . Given the potential of these molecules as therapeutic and imaging agents, we set out to investigate three new 4AP derivatives and their structure-activity relationships.…”
Section: Introductionmentioning
confidence: 99%